A gestão de pessoas como fator de gerência organizacional: análise do contexto em uma agência bancária do município de Itacoatiara -AM - Azevedo, Eduardo Soares de (Brasil, 2024)
It is through the adoption of a well-structured and well-founded model of development of productive activities that an enterprise can perform its tasks without major problems. This study aimed to analyze Strategic People Management and its consequences, aligned with the working relationship within a financial institution. Through the development of research activity regarding People Management within the AB Agency located in the municipality of Itacoatiara- AM, which has carried out its activities in the location for more than 20 years, seeking through the application of a questionnaire and SWOT tools and GUT, the understanding of how the financial institution develops its personnel management taking into account internal activities and the impact on the employee's quality of life and also on the quality of service. An exploratory and descriptive study with field research to collect information that later became observations, and graphic elements to present the data quantitatively, intending, therefore, to be a case study. In this way, the main results obtained were the positive perception of employees regarding the company's HR, and its standards and guidelines, however without showing dissatisfaction with the lack of support by the organization in listening to suggestions and ideas, in addition to perceiving the Integration of new employees is not very assertive, requiring adjustments. Keywords: People Management, SWOT, GUT, Bank branch, Itacoatiara/AM..